Dendritic cell-based immunotherapy - Sabado, Rachel L; Balan, Sreekumar; Bhardwaj, Nina (Cell research, 2017)
Immunotherapy using dendritic cell （DC）-based vaccination is an approved approach for harnessing the potential of a patient＇s own immune system to eliminate tumor cells in metastatic hormone-refractory cancer. Overall, al- though many DC vaccines have been tested in the clinic and proven to be immunogenic, and in some cases associated with clinical outcome, there remains no consensus on how to manufacture DC vaccines. In this review we will discuss what has been learned thus far about human DC biology from clinical studies, and how current approaches to apply DC vaccines in the clinic could be improved to enhance anti-tumor immunity.